Comparative Transcriptome Analysis Reveals the Specific Activation of Defense Pathways Against Globodera pallida in Gpa2 Resistant Potato Roots - Zheng, Qi; Bertran, André; Brand, Anouk; van Schaik, Casper C.; van de Ruitenbeek, Stefan J. S.; Smant, Geert; Goverse, Aska; Sterken, Mark G. (Frontiers in Plant Science, 2022)
Cyst nematodes are considered a dominant threat to yield for a wide range of major food crops. Current control strategies mainly dependent on crop rotation and the use of resistant cultivars. Various crops exhibit single dominant resistance (R) genes able to activate effective host-specific resistance to certain cyst nematode species and/or populations. An example is the potato R gene Gpa2, which confers resistance against the potato cyst nematode (PCN) Globodera pallida population D383. Activation of Gpa2 results in a delayed resistance response, which is characterized by a layer of necrotic cells formed around the developing nematode feeding structure. However, knowledge about the Gpa2-induced defense pathways is still lacking. Here, we uncover the transcriptional changes and gene expression network induced upon Gpa2 activation in potato roots infected with G. pallida. To this end, in vitro grown Gpa2 resistant potato roots were infected with the avirulent population D383 and virulent population Rookmaker. Infected root segments were harvested at 3 and 6 dpi and sent for RNA sequencing. Comparative transcriptomics revealed a total of 1,743 differentially expressed genes (DEGs) upon nematode infection, of which 559 DEGs were specifically regulated in response to D383 infection. D383-specific DEGs associated with Gpa2-mediated defense mainly relate to calcium binding activity, salicylic acid biosynthesis and systemic acquired resistance. These data reveal that cyst nematode resistance in potato roots depends on conserved downstream signaling pathways involved in plant immunity, which are also known to contribute to R genes-mediated resistance against other pathogens with different lifestyles.